Anti-bribery disclosures: A response to networked governance. Issue 1 (March 2018) - Islam, Muhammad Azizul; Dissanayake, Thusitha; Dellaportas, Steven; Haque, Shamima
Highlights: The study examines how network governance influences anti-bribery disclosures. 'Network governance' is derived from legitimacy and responsive regulation theories. Anti-bribery reporting is positively associated with the extent of media attention. Anti-bribery reporting is influenced by NGO pressures. Anti-bribery reporting tends to be symbolic rather than substantive. Abstract: This study examined the posited link between networked governance (the activities of NGOs and the media) and the anti-bribery disclosures of two global telecommunication companies. Based on a joint consideration of legitimacy theory, media agenda setting theory and responsive regulation, the findings show that anti-bribery disclosures are positively associated with the activities of the media and NGO initiatives. The findings also show that companies make anti-bribery disclosures to maintain symbolic legitimacy but are less prominent in effecting a substantive change in their accountability practices.